Penggunaan Media Digital Smart TV dalam Pembelajaran Sejarah Kebudayaan Islam untuk Meningkatkan Minat Belajar - Sugiyarti, Sri; Rohimah, Siti (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This study aims to analyse the impact of using Smart TV digital media in learning Islamic Cultural History (SKI) at MAN 2 Karanganyar, to explore how Smart TV can improve students' engagement, material understanding, and discussion skills. In addition, this study aims to determine the extent to which the use of Smart TV can improve the overall quality of learning in the school. The method used in this research is descriptive qualitative method with triangulation techniques, namely observation, interviews, and documentation with the subjects of students, teachers, vice principal for curriculum, and principal of MAN 2 Karanganyar. The results of this study are Smart TV in learning Islamic Cultural History (SKI) at MAN 2 Karanganyar has a significant positive impact, increasing student involvement, facilitating understanding of complex material, and reducing boredom in conventional learning. Through learning with interactive media such as videos, animations, and presentations allows students to learn in a more interesting and varied way.